2021
DOI: 10.21093/di.v21i1.3175
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Muslim Pre-Service Teachers’ Honesty on Cheating and Plagiarism: A Survey in Indonesian Islamic University

Abstract: Cheating and plagiarism have been crucial issues among students studying either at high school or undergraduate levels. This present study aims to reveal the cheating and plagiarism practices among pre-service teachers in their undergraduate program at one Islamic university in Indonesia. As Muslim teacher candidates, the respondents are urged to uphold academic integrity and honesty. Thus, this study seeks to provide data on how serious the academic ethics immersed in Muslim pre-service teachers. The method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This study used a set of questionnaires to collect quantitative and qualitative data. Following Farah (2021), a simple statistical analysis of percentage calculation was carried out through a close-ended questionnaire. This is because this study focused more on the qualitative aspect rather than on the quantitative one of the student's responses to the items in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used a set of questionnaires to collect quantitative and qualitative data. Following Farah (2021), a simple statistical analysis of percentage calculation was carried out through a close-ended questionnaire. This is because this study focused more on the qualitative aspect rather than on the quantitative one of the student's responses to the items in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on plagiarism and dishonesty had been conducted in various countries, but research on knowledge, behavior and experiences of university students of plagiarism is still rarely done in Indonesia. A recent study on university students' plagiarism in Indonesia was conducted by Farah (2021). She investigated Islamic university students' attitudes on cheating and plagiarism and found that the majority of her respondents reported that they never paid someone for an exam, never changed answers after their exam papers were scored but about 50% of them often copied other students' answers in the exam.…”
mentioning
confidence: 99%